A study of the effect on human mesenchymal stem cells of an atmospheric pressure plasma source driven by different voltage waveforms. (9th August 2016) - Laurita, R; Alviano, F; Marchionni, C; Abruzzo, P M; Bolotta, A; Bonsi, L; Colombo, V; Gherardi, M; Liguori, A; Ricci, F; Rossi, M; Stancampiano, A; et al.
Abstract: The effect of an atmospheric pressure non-equilibrium plasma on human mesenchymal stem cells was investigated. A dielectric barrier discharge non-equilibrium plasma source driven by two different high-voltage pulsed generators was used and cell survival, senescence, proliferation, and differentiation were evaluated. Cells deprived of the culture medium and treated with nanosecond pulsed plasma showed a higher mortality rate, while higher survival and retention of proliferation were observed in cells treated with microsecond pulsed plasma in the presence of the culture medium. While a few treated cells showed the hallmarks of senescence, unexpected delayed apoptosis ensued in cells exposed to plasma-treated medium. The plasma treatment did not change the expression of OCT4, a marker of mesenchymal stem cell differentiation.